GAMBARAN IMPLEMENTASI PROGRAM JAMINAN KESEHATAN NASIONAL DI RUMAH SAKIT IBU DAN ANAK HARAPAN BUNDA TAHUN 2016 - Rahayu, Pande Made Sri; Indrayathi, Putu Ayu (ARCHIVE OF COMMUNITY HEALTH; Vol 4 No 1 (2017): Juni (2017), 2019)
ABSTRACT In an effort to achieve Universal Health Coverage in 2019, all health providers are expected to work together including private provider. RSIA Harapan Bunda as one of the secondary health facilities, in collaboration with BPJS Kesehatan starting in March 2015. The aim of this research was to find out the description of the implementation of the JKN program at RSIA Harapan Bunda. This research is a qualitative descriptive design research. Data collection is done by in-depth interviews with respondents who have been determined by purposive sampling method as many as 13 people. The study found that, RSIA Harapan Bunda need for 6 months in order to implement and receive JKN patients. Preparation of the establishment of a team responsible for implementing JKN in hospitals and facilities. Nominal gains during the 1 year implementation have not yet been obtained, only the community is getting to know RSIA Harapan Bunda so that patient visits increase. Medical staff provide the same service to general patients and JKN user patients, based on the SOP set by the hospital. Medical support staff have been trained in the use of the INA-CBGs program in hospitals. Patients as recipients of health services were greatly helped by the JKN program. The procedure for obtaining health services is known, but there are still patients who do not understand well so there is a misunderstanding with the hospital registration officer. Socialization to unite the perceptions and commitments of each component of the hospital so that all employees can understand this program and know what things should be sought to realize cost effective health services. Keywords: Implementation, National Health Insurance, RSIA